The differences between the qualification and final results in the jumping disciplines of the finalists of European Indoor Championship in Prague 2015 - Pavlovic, R.; Milicevic, L.; Vrcic, M.; Pupis, M. (Acta Kinesiologica, 2016)
The aim of this study was to identify differences between athletes in jumping disciplines of European Indoor Championships held from 6-8 March 2015 in Prague. The sample included 66 athletes (33 female and 33 male), who participated in the qualifiers and finals. The results achieved in qualification and final appearances have been analyzed in four official jumping events (long jump, triple jump, high jump, pole vault). Using the module's t-test the results were obtained that showed that 56% of male and female athletes in all disciplines achieved better final than the qualifying result, while 28% achieved a better result in qualifying than in the final. Also 14% of the athletes achieved the same result in both appearances (disciplines high jump, pole vault). Statistically significant differences for the level (p<0,05) between the qualifications and finals were recorded in the disciplines of long jump (women) and triple jump (men).